2016
DOI: 10.4172/0974-8369.1000361
|View full text |Cite
|
Sign up to set email alerts
|

Local Thermal Impact on Microcirculation Assessed by Imaging Photoplethysmography

Abstract: Laser Doppler Flowmetry and Laser Speckle Contrast Imaging are applied usually for assessment of parameters of the cutaneous blood flow during thermoregulation. Alternatively, this work explores the feasibility of blood pulsation imaging under incoherent green illumination for measuring the response of human body on local thermal impact. The proposed technique allows assessment of the cutaneous blood flow changes during thermoregulation simultaneously in different areas of the body. The preliminary experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The cost-effective alternative could be remote photoplethysmography [ 26 ], which is a contactless optical technique for blood volume pulsation detection in the tissue using various computational algorithms [ 27 ] and relatively simple instrumentation: video camera, to detect subtle variations of back-reflected light, and appropriate light source. Currently, the imaging photoplethysmography (iPPG) is expanding its applications beyond the assessment of heart rate and arterial stiffness, illustrated by previous studies such as studies of Kamshilin et al suggesting the high clinical potential of remote photoplethysmography in the evaluation of cutaneous vasomotor responses [ 27 , 28 , 29 , 30 , 31 , 32 ]. However, further refinement of this approach requires alteration of small sensory nerve fiber function in a controllable manner, which is difficult to achieve in neuropathic patients due to differences in etiology, degree of dysfunction, comorbidities, and other factors [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…The cost-effective alternative could be remote photoplethysmography [ 26 ], which is a contactless optical technique for blood volume pulsation detection in the tissue using various computational algorithms [ 27 ] and relatively simple instrumentation: video camera, to detect subtle variations of back-reflected light, and appropriate light source. Currently, the imaging photoplethysmography (iPPG) is expanding its applications beyond the assessment of heart rate and arterial stiffness, illustrated by previous studies such as studies of Kamshilin et al suggesting the high clinical potential of remote photoplethysmography in the evaluation of cutaneous vasomotor responses [ 27 , 28 , 29 , 30 , 31 , 32 ]. However, further refinement of this approach requires alteration of small sensory nerve fiber function in a controllable manner, which is difficult to achieve in neuropathic patients due to differences in etiology, degree of dysfunction, comorbidities, and other factors [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that our previous experiments, in which applicability of an IPPG system to assess the microvasculature response on the temperature changes [12] was demonstrated, were carried out in conditions under which the temperature of a preliminarily-cooled finger was increased due to internal heating. In contrast, here we assessed the microcirculation reaction to the external local thermal impact with the temperature exceeding the skin temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, it was shown that changes in skin blood flow measured by LDF and PPG are related to changes in the skin temperature [11]. Recently, the possibility of quantifying the change in blood microcirculation with local temperature effects on the human hand has been demonstrated by using the imaging photoplethysmography (IPPG) system [12]. It is worth noting that the PPG waveform was measured by Kamshilin et al [12] only afterwards the thermal impact.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigation of the skin and muscular vessels reaction on differential provocations is very useful for deeper understanding of the PPG signal origin. For example, local change of the skin temperature results in local change of blood flow in the dermis 30 affecting the PPG signal 31 , whereas global hypothermia affects the blood flow in muscular vessels, which maximally contribute to the volumetric blood flow of the forearm 32 . In our extended experiment, the skin temperature was the same.…”
Section: Discussionmentioning
confidence: 99%